Culture your culture : innovating experiences @Work - Jaw-Madson, Karen (Emerald Publishing Limited, 2018)
Culture Your Culture is the comprehensive guide to Design of Work Experience, an innovative (and much needed) framework for the design and implementation of culture, people strategies, organizational change, and designed experiences that enable both business and people thrive.